The Influence of Influence Service Quality Tax on Land and Building Tax Revenue in Rular and Urban Sector in The Gelumbang Sub-District of Muara Enim. - Ida Zuraida (Integritas Jurnal Manajemen Profesional (IJMPRO), 2020)
The formulation of the problem study was how the influence of Influence Service Quality Tax on Land and Building Tax Revenue in Rular and Urban Sector in the Gelumbang sub-district of Muara Enim. This study was aimed to find out the service quality tanx on land and building tax revenue in rural and urban sector in the Gelumbang sub-district of Muara Enim. This study was type associative research. The research sample in this study used 99 samples with a purposive sampling technique by slovin formula. The data used in this study was primary data taken by questionnaire. The techniques analysis used were regression linear simple and test the hypothesis. The results of the research found that the Service Quality Tax gave an influence on Land and Building Tax Revenue in Rural and Urban Sector in the Gelumbang sub-district of Muara Enim.